Removal of crystal violet from wastewater using ZNCL2 activated Crescentia Cujete carbon: Adsorption isotherm and kinetics - P. BABY SHAKILA, (International Journal of Pharma and Bio Sciences, 2018)
Crescentia cujete (CC), an agricultural solid waste, was used for the development of activated carbon by zinc chloride activation (ZACC). The carbon was employed as an adsorbent for the removal of cationic dye Crystal Violet (CV). Batch adsorption experiments were carried out to study the effects of various parameters such as contact time, initial dye concentration, adsorbent dose and initial solution pH. Lagergren first-order, pseudo second-order and intraparticle diffusion kinetic models were used to identify the possible mechanisms of adsorption process. The adsorption of CV follows pseudo-second-order model. The adsorption isotherm models of Langmuir, Freundlich and D-R were used for the mathematical description of the adsorption equilibrium, and the experimental data fitted very well with the Langmuir model. The maximum adsorption capacity (Qo) obtained was 24.39 mg g−1 at a temperature of 35 °C. Maximum adsorption occurred at pH 10.0. Desorption studies shows that the regeneration of the adsorbent can be easily achieved.